The Effect of Constructivist Learning on Science Literacy and Students' Learning Outcomes - Joko Suroso; Sukamto Sukamto; Lilis Putri Wijayanti; Ihsaniatun Nur Alifah; Nourma Yulita (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
The present study has been conducted with a view to ascertaining the extent to which implementing a constructivist learning model influences science literacy and students' cognitive learning outcomes (achievement). The research methodology employed is a quasi-experimental design, characterized by a pretest-posttest design with a control group. Sample selection was purposive, with the research subjects divided into an experimental class receiving constructivist treatment and a control class receiving conventional instruction. The research instrumentation encompassed a science literacy diagnostic test, a learning outcome evaluation test, and an observation sheet to validate the learning implementation process. Inferential data analysis was performed using an independent t-test and the calculation of normalized gain scores. The research findings indicate that constructivist learning has a significant influence on enhancing both learning outcomes and science literacy among students (significance level 0,00 < 0.01). In comparison, the experimental class demonstrated an average post-test learning outcome score of 65 points, which was significantly higher than the 42 points achieved by the control class. In addition, the mean science literacy score for the experimental class was 73.17, higher than that of the control class (61.37). Consequently, it can be concluded that constructivist learning is effective within the context of science instruction. This approach has the potential to optimise learning outcomes and reinforce students' science literacy. The present study proposes adopting constructivism as a pedagogical strategy to foster students' conceptual understanding and participatory engagement